Biomineralization: An Opportunity and Challenge of Nanoparticle Drug Delivery Systems for Cancer Therapy. Issue 22 (11th October 2020) - Wang, Weicai; Liu, Xiaofan; Zheng, Xiangjiang; Jin, Hyung Jong; Li, Xuemei
Abstract: Biomineralization is a common process in organisms to produce hard biomaterials by combining inorganic ions with biomacromolecules. Multifunctional nanoplatforms are developed based on the mechanism of biomineralization in many biomedical applications. In the past few years, biomineralization‐based nanoparticle drug delivery systems for the cancer treatment have gained a lot of research attention due to the advantages including simple preparation, good biocompatibility, degradability, easy modification, versatility, and targeting. In this review, the research trends of biomineralization‐based nanoparticle drug delivery systems and their applications in cancer therapy are summarized. This work aims to promote future researches on cancer therapy based on biomineralization. Rational design of nanoparticle drug delivery systems can overcome the bottleneck in the clinical transformation of nanomaterials. At the same time, biomineralization has also provided new research ideas for cancer treatment, i.e., targeted therapy, which has significantly better performance. Abstract : Biomineralization is a common process in organisms to produce hard biomaterials by combining inorganic ions with biomacromolecules. In the past few years, biomineralization‐based nanoparticle drug delivery systems for cancer treatment have gained a lot of research attention due to the advantages including good biocompatibility, degradability, and targeting. This work aims to promote future researches on cancer therapy based on biomineralization.